A Study of Knowledge and Attitudes of Health Students towards Acute Respiratory Infections (ARI) in Lubuklinggau City - Nabela, Putri; Alarsan, Sami; Hue, Phung Thi Kim (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: The aim of this research was to determine the relationship between knowledge and attitudes of health students towards Acute Respiratory Tract Infections in Lubuklinggau City.Methodology: This research method uses quantitative correlational research. The population in this study were all health students in semester 1 and semester 3 in the city of Lubuklinggau. The samples taken were 72 respondents. The sampling technique uses simple random sampling through questions that have been tested for validity and reliability. The data analysis technique uses a correlation test.Main Findings: The results of this research are that there is a relationship between knowledge and attitudes of health students, the results of knowledge and attitudes have good value for acute respiratory infections.Novelty/Originality of this study: This research provides valuable insight into efforts that may be needed to increase awareness and engagement in fighting this Acute Respiratory Infection disease at the local level. It is hoped that the findings from this research can help in designing more effective educational programs and more focused prevention strategies to mitigate Acute Respiratory Infections in Lubuk Linggau and the surrounding area.